ALUMNI MENURUT PERSPEKTIF TOTAL QUALITY MANAGEMENT (TQM) - Kharisul Wathoni (IAIN Ponorogo, 2021)
Alumni have a strategic role including improving the quality of education and developing various extracurricular activities in schools and alumni who have competence can play an important function in building public opinion to attract new students and public. This article discusses the role of alumni according to the Total Quality Management (TQM) perspective to find out related matters, namely the understanding and role of alumni, how the characteristics of integrated quality schools and how alumni management is according to the TQM perspective. The results of the analysis show the characteristics of quality schools have 5 quality pillars which include a focus on customers, total involvement, measurement, commitment and continuous improvement. The pillars are based on school beliefs. Alumni are able to make many contributions in improving the quality of education, therefore there is a need for alumni management. Alumni management includes the development of alumni networks, alumni construction of educational institutions, institutional governance of alumni management and methods for tracing alumni data through electronic and social media.Keywords: Alumni, educational institutions, schools, total quality management.